Occupational Stress and Psychological Wellbeing Among Physicians Working in the Emergency Departments of Selected Tertiary Hospitals - Atikah Islam Chowdhury; MD. Hassan Sazu (Goodwood Publishing, 2026)
Purpose: This study aimed to assess occupational stress and its relationship with psychological well-being among physicians working in the emergency departments of tertiary hospitals in Dhaka, Bangladesh, and to determine key occupational factors that may affect stress levels and mental health outcomes. Research Methodology: This study was conducted on 110 emergency physicians in Dhaka, using the Health Professionals Inventory Scale (HPIS) to measure occupational stress and the WHO-5 Well-Being Index to assess psychological well-being. The survey also collected demographic information and data on job satisfaction and employment types. Results: The study findings revealed that 57.3% of respondents experienced very high occupational stress, and 41.8% reported good psychological well-being. A significant inverse relationship between stress levels and well-being was observed, indicating that higher occupational stress was associated with poorer psychological health. Employment type and job satisfaction were identified as critical factors influencing stress and well-being. Conclusions: Occupational stress represents a significant challenge for emergency physicians and requires organizational interventions, including workload management, psychological support, and improved workplace conditions. Limitations: The cross-sectional design, self-reported measures, limited sample size, and concentration of participants in tertiary hospitals in Dhaka restrict the generalizability and causal interpretation of the findings. Contributions: This study provides empirical evidence for healthcare administrators and policymakers to develop targeted strategies for reducing occupational stress and strengthening psychological well-being among emergency physicians.